Low prevalence of latent autoimmune diabetes in adults in northern India. Issue 6 (12th December 2014) - Sachan, A.; Zaidi, G.; Sahu, R. P.; Agrawal, S.; Colman, P. G.; Bhatia, E.
Abstract Aim To study the frequency of islet antibodies in a large cohort of clinic‐ and community‐based patients with Type 2 diabetes in northern India. Methods We measured glutamic acid decarboxylase (GAD) antibodies in 618 adults with Type 2 diabetes (378 patients with diabetes attending a hospital clinic, 240 patients diagnosed in a community survey) and in 192 healthy subjects residing in north India. Islet antigen 2 (IA2) antibodies were also studied in a proportion of the patients with diabetes (n = 492) and in a control population (n = 191). GAD and IA2 antibodies were measured by immunoprecipitation of the respective 35S‐labelled recombinant antigen. Results We found that GAD antibodies were present in nine (1.5%) patients with diabetes (clinic population: 0.8%, community study: 2.5%), a prevalence similar to that among the subjects without diabetes (n = 2; 1%). IA2 antibodies were detected in seven patients with Type 2 diabetes (1.4%) and in two healthy control subjects (1.0%). The frequency of either GAD or IA2 antibodies was similar in people with and without diabetes (3.2 vs 2.1%). No subject was found to have both antibodies. Insulin requirement was higher among antibody‐positive than among antibody‐negative patients (GAD antibody: 33 vs 6.3%; P = 0.001; GAD or IA2 antibody: 23.1 vs 6.4%; P = 0.02); however, other clinical features were similar in the two groups. Conclusions In the present north‐Indian population with Type 2 diabetes, the overall prevalence of GAD antibodies and the prevalence of either GAD or IA2 antibodies were considerably lower than those reported in white European populations.